2009
DOI: 10.1111/j.1834-7819.2008.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple, large sialoliths of the submandibular gland duct: a case report

Abstract: This paper reviews the major clinical and radiographic features of sialoliths and illustrates these with an unusual case of multiple sialoliths within the submandibular gland duct. The differential diagnosis of other calcific structures both within and outside the salivary gland that may mimic a sialolith is also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 19 publications
0
29
0
2
Order By: Relevance
“…We found no parotid sialoliths in this study, and the incidence of these sialoliths is reportedly small, in 10%e20% of all sialoliths (Kesse et al, 1998). The high concentrations of calcium and phosphate and the more viscous mucous content of saliva cause more sialoliths in the submandibular gland (Huang et al, 2009). However, as a diagnostic tool, 3-D imaging is a significant aid in identifying parotid stones (Mandel and Hatzis, 2000).…”
Section: Sialolithiasis Parotis and Submandibularis (Sp And Ssub)mentioning
confidence: 45%
See 1 more Smart Citation
“…We found no parotid sialoliths in this study, and the incidence of these sialoliths is reportedly small, in 10%e20% of all sialoliths (Kesse et al, 1998). The high concentrations of calcium and phosphate and the more viscous mucous content of saliva cause more sialoliths in the submandibular gland (Huang et al, 2009). However, as a diagnostic tool, 3-D imaging is a significant aid in identifying parotid stones (Mandel and Hatzis, 2000).…”
Section: Sialolithiasis Parotis and Submandibularis (Sp And Ssub)mentioning
confidence: 45%
“…However, we did not find this to be predominant in either sex in this study. Sialolithiasis can appear at any age (Huang et al, 2009;Mandel and Hatzis, 2000), with rare cases being reported in children (Bodner and Fliss, 1995). Parotid duct stones are smaller than submandibular stones and occur more frequently in the third and fourth decades of life (Mandel and Hatzis, 2000).…”
Section: Sialolithiasis Parotis and Submandibularis (Sp And Ssub)mentioning
confidence: 99%
“…23 To our best knowledge, the sialolith presented in this case is one of the largest reported to date, as compared with the published data (Table 1). No report has mentioned about the width which in this case was almost an inch.…”
Section: Discussionmentioning
confidence: 55%
“…Sialolithes can be identified well in panoramic and periapical radiographs. In case of multiple stones and/or when their positions cannot be clearly detected with routine radiographs; sialography, ultrasound, sialoendoscopy, CT and magnetic resonance sialographies can be helpful for diagnosis (6). In our case, we were benefited from ultrasonography and CT examinations to verify the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Large sized stones can be palpated inside the duct (5). Although the most commonly used imaging techniques for the diagnosis of sialolithes are occlusive and panoramic graphs, ultrasonography (US) and sialography; recently can be benefited from computerized tomography (CT), magnetic resonance sialography and sialoendoscopy methods too (6). While transoral approach is preferred for the treatment of the stones observed close to the perihilar region of the gland or mouth floor, submandibular gland excision treatment is used for the stones inside proximal duct or parenchyma (7).…”
Section: Introductionmentioning
confidence: 99%